Studi Komparatif KitÄb RijÄl Sunni dan SyÄ«ah (Studi atas KitÄb Tadzkirah al-HuffÄzh Karya al-Dzahabi dan KitÄb al-RijÄl Karya DÄwud al-Hulli) - Rohmansyah, Rohmansyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2017)
Study the book of Hadith is a great importance to study, especially the study of rijÄl al-hadÄ«th, such as Tadzkirah al-Huffazh of al-Dzahabi, Sunni versions, and KitÄb al-RijÄl of al-Hulli, Syi'i version. This research was conducted with descriptive analytical approach and historical approach. This study found that both books discuss the rijÄl al-hadÄ«th (the narrators of hadith) from the aspect of quality that is structured in the systematic style of the book of Mu'jam. The difference is that the Sunni rijÄl al-HadÄ«ts are the companions of the Prophet, the tabi'in and so on, while the Shi'ite rijÄl al-hadÄ«th is the Ahl al-Bait which is attributed to the figure of Ali bin Abi Talib. Historically, the two books are composed from the historical background behind it. The Book of Tadzkirah al-Huffazh is structured as an attempt to legitimize narrators and memorizers of Hadith from amongst shahabah, tabi'in, and so on. Meanwhile, the KitÄb al-RijÄl version of the Shi'ah also wanted to prove the greatness of their companions from the ahl al-Bait people attributed to Ali ibn Abi Talib.